(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2026)
Delay discounting refers to the tendency to subjectively devalue rewards as the delay to their receipt increases. High levels of discounting are associated with maladaptive behaviors and clinical conditions such as anxiety and depression. This study investigated the influence of delay discounting on symptoms of anxiety, depression, and stress in 520 Brazilian adults (70.2% women; mean age = 27.3 years), while controlling for sociodemographic covariates and the personality trait of neuroticism. Participants completed online questionnaires on personality (IGFP-5), psychopathological symptoms (DASS-21), and monetary preferences (MCQ-27). Results showed that individuals with high discounting exhibited higher levels of anxiety, depression, and stress compared to those in the moderate and low discounting groups. However, after adjusting for sociodemographic variables and neuroticism, only anxiety and stress symptoms remained significantly associated with high discounting. These findings suggest that delay discounting influences specific symptoms of internalizing disorders.